The Urgency of Participatory Leadership in Schools - Gunvor Hallström (CV Edujavare Publishing, 2025)
Participatory leadership has become increasingly important in contemporary schools due to the growing complexity of educational management, rapid technological advancement, and the demand for collaborative decision-making. Unlike traditional hierarchical leadership, participatory leadership actively involves teachers, staff, students, and other stakeholders in planning, implementing, and evaluating school policies. Such an approach strengthens organizational commitment, enhances teacher motivation, fosters professional collaboration, and creates a positive school climate that supports continuous improvement. Previous studies indicate that participatory leadership indirectly contributes to improved teaching quality and student achievement by empowering educators and encouraging collective responsibility. Moreover, schools that embrace participatory leadership demonstrate greater adaptability to educational reforms and innovation because decision-making is distributed across organizational members rather than concentrated solely in the principal. In an era characterized by educational uncertainty and increasing accountability, participatory leadership represents a strategic approach for promoting sustainable school development, strengthening institutional resilience, and ensuring that educational goals are achieved effectively. Therefore, this study highlights the urgency of implementing participatory leadership as a fundamental strategy for improving school effectiveness and educational quality in the twenty-first century.